2004
DOI: 10.1021/ma0350922
|View full text |Cite
|
Sign up to set email alerts
|

Chain-Length Dependence of Termination Rate Coefficients in Acrylate and Methacrylate Homopolymerizations Investigated via the SP−PLP Technique

Abstract: Termination rate coefficients, kt, of alkyl acrylate and alkyl methacrylate homopolymerizations at 40°C and pressures of 1000 and 2000 bar have been measured up to high degrees of monomer conversion using the time-resolved single-pulse-pulsed-laser polymerization (SP-PLP) technique. The chain-length dependence (CLD) of k t has been deduced from SP-PLP data by adopting the power-law model, kt ) k t 0 i -R , where i is the chain length. For methacrylates at low degrees of monomer conversion, R is close to the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
65
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 34 publications
11
65
0
Order By: Relevance
“…[131] Using the time-resolved singlepulse pulsed-laser-polymerization technique (SP-PLP), Buback et al [132] were able to measure k t values up to high degrees of monomer conversion. They verified the value of e as being close to 0.16 for methacrylates but only at low degrees of monomer conversion.…”
Section: Chain Length Dependent Terminationmentioning
confidence: 99%
“…[131] Using the time-resolved singlepulse pulsed-laser-polymerization technique (SP-PLP), Buback et al [132] were able to measure k t values up to high degrees of monomer conversion. They verified the value of e as being close to 0.16 for methacrylates but only at low degrees of monomer conversion.…”
Section: Chain Length Dependent Terminationmentioning
confidence: 99%
“…Moreover, it needs to be noted that the a value from SP-PLP-ESR is higher than the SP-PLP-NIR value of a ¼ 0.15 AE 0.04. [13] This is probably due to the fact that the NIR technique, which is applied at higher temperatures, primarily catches the chain-length dependence of k t for larger radicals, which is weaker than the one for small radicals (see below).…”
Section: Experimental Partmentioning
confidence: 99%
“…Buback et al recently reported circumstantial evidence for the presence of MCR in acrylate polymerization using the single-pulse PLP method. [34] It was postulated that the MCR content increased with increasing size of the ester alkyl group and with decreasing monomer concentration. Furthermore, rapid termination of the expelled radical by b-fragmentation of MCR might provide a faster pathway than termination reactions involving MCR leading to faster overall termination.…”
Section: Determination Of Apparent K P and K T Valuesmentioning
confidence: 99%